Esthetic rehabilitation possibilities in pediatric dentistry: literature review (Research, Society and Development, 2022)
The rehabilitation of destroyed teeth aims to reestablish the function and esthetics of patients. Thanks to the improvement of dentistry, various restorative possibilities can be used in dentistry. The rehabilitating materials and restorative techniques in the current era are vast, so the choice of technique has to fit the patient biologically, aesthetically, functionally, financially and psychologically. The aim of this work is to examine the aesthetic rehabilitative possibilities in pediatric dentistry, considering the various techniques and materials for this purpose, and to provide education and awareness regarding the importance of maintaining good oral health. The development of this study was based on a narrative review of the literature, in which the guiding question of the study was: "What are the best rehabilitative techniques to recover the aesthetics and functionality of anterior teeth and what are the problems that the destruction of these teeth brings to the child's life?". The searches were performed using the PubMed and VHL databases, and data were collected by reading the abstracts and the full texts. Based on this, it is clear that there are several alternatives that can be used to restore the aesthetics and/or function of a tooth that has been compromised, either by trauma or by carious lesion, including resin restorations, acetate crowns and zirconium crowns. Thus, it is up to the pediatric dentist together with the family to decide which is the best choice among the materials available for the treatment of the child.